MANAJEMEN PEMBELAJARAN MATEMATIKA BERBASIS TIK (TEKNIK ILMU KOMPUTER) - Muhamad Rifan; Ahmad Kurniawan, Arsal Bagus Anugrah, Irvan Wahid Aditya, Yoga Mardiansyah Rahman, Nur Asyam Wijaya, (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study discusses the application of Information and Communication Technology (ICT) in mathematics learning through the use of storyboard-based instructional videos as an effort to improve the quality of the learning process and student graduation outcomes. Developments in educational technology require teachers to create lessons that are more engaging, interactive, and easy to understand, especially for mathematics, which is abstract in nature. The research methods used include literature review, interviews, observation, and documentation study with a qualitative approach. Based on the results, ICT-based mathematics teaching is implemented through stages of planning, implementation, evaluation, and follow-up by utilizing digital media such as animations, instructional videos, digital presentations, and technology-based modules. Storyboards play a role in helping teachers arrange the flow of material delivery in a structured way so that mathematical concepts can be presented more visually and communicatively. The use of digital media has also been shown to increase learning motivation, participation, and students’ understanding in both online and face-to-face learning. Although some challenges remain, such as limited technological facilities and internet access, using ICT in mathematics instruction still contributes positively to teaching effectiveness and the quality of school graduates.